1963
DOI: 10.1063/1.1701425
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Zinc Oxide Nuclei

Abstract: Synthesis and local structure of doped nanocrystalline zinc oxides

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1971
1971
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…It has been demonstrated that ZnO nuclei possess a “fourling” structure19 from which multiple (ideally four or seven) spines will possibly develop along their own [001] directions 20. If those spines are able to grow unconstrained under hydrothermal conditions, star‐like or flower‐like ZnO particles or nanostructures are produced, which have been reported extensively in previous literature,18, 21 and also exist in our films (e.g.…”
mentioning
confidence: 72%
“…It has been demonstrated that ZnO nuclei possess a “fourling” structure19 from which multiple (ideally four or seven) spines will possibly develop along their own [001] directions 20. If those spines are able to grow unconstrained under hydrothermal conditions, star‐like or flower‐like ZnO particles or nanostructures are produced, which have been reported extensively in previous literature,18, 21 and also exist in our films (e.g.…”
mentioning
confidence: 72%
“…Fig. 3 displays the SEM images of the films prepared by exposed to atmosphere for 6,9,12,15,18,21 compact density of the ZnO NWAs increases and the diameter decreases. In addition, when the exposure time reaches 15 min, the ZnO NWAs exhibit the most uniform, dense, and thin arrays.…”
Section: Structural and Morphological Characterizationmentioning
confidence: 98%
“…It has been demonstrated that ZnO nuclei possess a "fourling" structure [21] from which multiple spines will possibly develop along their own [0 0 1] directions. After the cover glass was removed, the initiation of fourlings started by homogeneous nucleation near the solution surface.…”
Section: Growth Mechanism Of Self-supporting Zno Nwasmentioning
confidence: 99%
“…It is predicted that the secondary growth might be due to the fact that the ionic radius of Ga (∼ 0.62 Å) is smaller than the ionic radius of the Zn (∼ 0.74 Å) so when a large number of Ga ions is incorporated into the lattice of the ZnO they cause strain and hence distortion of the primary growth. [22][23][24][25] This distortion helps in the formation of multipod structures as the distorted sites of the crystal act as the active sites for the secondary growth.…”
Section: Morphological Compositional and Structuralmentioning
confidence: 98%